2023
DOI: 10.3390/molecules28020525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epigallocatechin-3-Gallate on Matrix Metalloproteinases in Terms of Its Anticancer Activity

Abstract: Epidemiological studies have shown that the consumption of green tea has beneficial effects against cancer. Basic studies have provided evidence that epigallocatechin gallate (EGCG) is a major contributor to these effects. Matrix metalloproteinases (MMPs) are zinc-dependent metalloproteinases with the ability to degrade the extracellular matrix proteins and are involved in various diseases including cancer in which MMPs have a critical role in invasion and metastasis. In this review, we discuss the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…The inhibitory activity against MM rivative with higher bioavailability was stronger than that of CUR. These fi useful to develop an effective inhibitor of MMP2 which is involved in vari EGCG MDA of the active MMP2-EGCG complex revealed binding cavity of 10 A°around the active site residue Glu404 and that Ala192, Leu399, His403, Glu404, and Met421 are located close to the EGCG binding site [2,139]. The 15 amino acid residues (Trp151, Leu190, Leu191, Ala192, His193, Phe207, Trp213, Leu397, Leu399, Val400, His403, Glu404, Met421, Tyr425, and Tyr427) have an interaction energy of >2 kcal/mol.…”
Section: Curmentioning
confidence: 98%
See 1 more Smart Citation
“…The inhibitory activity against MM rivative with higher bioavailability was stronger than that of CUR. These fi useful to develop an effective inhibitor of MMP2 which is involved in vari EGCG MDA of the active MMP2-EGCG complex revealed binding cavity of 10 A°around the active site residue Glu404 and that Ala192, Leu399, His403, Glu404, and Met421 are located close to the EGCG binding site [2,139]. The 15 amino acid residues (Trp151, Leu190, Leu191, Ala192, His193, Phe207, Trp213, Leu397, Leu399, Val400, His403, Glu404, Met421, Tyr425, and Tyr427) have an interaction energy of >2 kcal/mol.…”
Section: Curmentioning
confidence: 98%
“…−57.61 kcal/mol (10) (Leu199, Phe234, His239, Glu240, Met257, Gln262) Amino acid residues involved in hydrogen bonding are indicated in parentheses. The binding energies were taken from the following references: (1) Zhang, Z. et al [134], (2) Li, F. et al [140], (3) Erusappan, T. et al [141], (4) Xu, J. et al [142], (5) Pandey, A.K. et al [143], (6) Yu, J. et al [147], (7) Huynh, C.B.…”
Section: Mmp14mentioning
confidence: 99%
“…At the molecular level, polyphenols may downregulate the ROS-induced activation of ERK 1/2, p38 and JNK, as well as PI3K/AKT, preventing the nuclear translocation of NF-kB and the downstream activation of the transcription factor AP-1. The consequent downregulation of MMP gene transcription results in the inhibition of tumor cell growth, metastasis, angiogenesis and inflammation [22,40,41]. As a result of our experiments, RSV inhibited MMP-9 in THP-1 supernatants but not in "in-gel" zymography, suggesting that this antioxidant only exerted its inhibitory action on the expression of the enzyme.…”
Section: Discussionmentioning
confidence: 61%
“…EGCG exhibits antioxidant properties to prevent the production of reactive oxygen intermediates, which are produced in the UVR stress photodamages. The study revealed that the potential mechanism of EGCG in protecting against UVA damage is closely related to its potent antioxidant effects and the ability to regulate genes expressions in human fibroblasts or retinal pigment epithelium (RPE) cells [ 10 , 27 ]. EGCG as potential natural chemopreventive agents during exposure to UVB-induced DNA damage in keratinocytes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%